Biomechanical comparison of a novel triangular fixation stem and a conventional fixation stem in a model of a prosthesis for ultrashort residual proximal femur reconstruction: a finite element analysis study - Zi-Wei Hou; Kai Zheng; Xiu-Chun Yu (BMC Musculoskeletal Disorders)
Abstract Background Reconstruction using a megaprosthesis is the primary method for treating long segmental bone tumors in the extremities following resection. However, conventional stem (CS) prostheses fail to provide stable fixation in the metaphysis. To improve prosthetic fixation in the proximal femoral metaphysis, in a previous study, we proposed a novel triangular fixation stem (TFS) design. The purpose of the present study was to use the finite element analysis (FEA) method to compare biomechanical properties of models of the TFS and CS prostheses for ultrashort residual proximal femur (URPF) reconstructions. Methods FEA was performed using a commercially-available software package and a Sawbones femur model subjected to a static load of 2800 N. This load simulated the weight of an adult weighing 70 kg doing a squat. The parameters determined were von Mises stress distribution, maximum von Mises stress, displacement distribution, and maximum displacement in different parts of the model, such as the femur and the prosthesis. Results The TFS prosthesis exhibited a more even von Mises stress distribution stress compared to the CS prosthesis. The maximum von Mises stresses on the prosthetic stem surface were 68.99 MPa and 85.91 MPa for the TFS and CS models, respectively. In the TFS model, the maximum von Mises stresses in the lateral plate and the screws were 115.28 MPa and 122.25 MPa, respectively. Regarding von Mises stresses distribution in the femur, the TFS model showed 26.80 MPa and 34.71 medially and laterally, respectively, whereas the CS model displayed 34.21 MPa and 20.36 medially and laterally, respectively. In the TFS model, maximum displacements were 0.51 mm in the femur and 0.18 mm in the prosthesis, with the corresponding values in the CS model being 0.71 mm and 0.30 mm, respectively. Conclusion The von Mises stress distribution of the model containing the TFS prosthesis is more even than that containing the CS prosthesis. Thus, the TFS prosthesis may be promising for use as prosthetic implantation in the reconstruction of a URPF.